Screening for HIV and hepatitis C virus using saliva tests in a prison in Ghana. A study of the prevalence and the status of knowledge - Ljungdahl, M.; Rie, C.M.; Gyan, B.A.; Hagbe, F.S.; Britton, S. (Lakartidningen, 2012)
HIV and HCV infection are two serious blood-borne diseases, more common among prisoners and prison officers than in the general population. In this study, the prevalence of HIV and HCV among prisoners and prison officers was investigated in a Ghanaian prison, using saliva tests. A questionnaire examined risk behaviour and knowledge of the diseases. The results showed a HIV prevalence of 2.6% and HCV prevalence of 2.3%. Furthermore, wariness concerning HIV and HCV was observed, more profound among inmates than officers. HIV and HCV prevalence in the Ghanaian prison ward was unexpectedly low. Saliva-based quick tests should be used for screening in prisons, because of poor hygiene standards and fear of needles; the HCV test, though, would need further validation. There is a need to improve the prevention of HIV and HCV transmission in prisons of Ghana, by increased testing and education, in order to reduce illness and stigmatisation.
Screening för HIV och hepatit C-virus med salivtest på ett fängelse i Ghana. Studie av prevalens och kunskapsläge
Keywords: HIV; HCV; blood-borne diseases; prisoners; prison officers; Ghanaian prison